2007
DOI: 10.1111/j.1468-0297.2007.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Cooperation in Trust Games

Abstract: It is well known in evolutionary game theory that population clustering in Prisoner's Dilemma games allows some cooperative strategies to invade populations of stable defecting strategies. We adapt this idea of population clustering to a two-person trust game. Without knowing it, players are typed based on their recent track record as to whether or not they are trusting (Players 1) and whether or not they are trustworthy (Players 2). They are then paired according to those types: trustors with trustworthy type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Just because people cannot be relied upon to backward induct with mindful rationally, does not mean that their socially This interpretation is consistent with trust game data reported by Rigdon, et al (2007) in which subjects are allocated randomly between two repeat play treatments: in the control each trial rematches subjects in pairs at random; in the research treatment subjects are rank ordered on each trial by frequency of historical cooperation over the previous five decision trials, and then matched according to these "trust" and "trustworthy" scores.…”
Section: Money (It Is Not the Standard Interactive Game In Which Paysupporting
confidence: 78%
“…Just because people cannot be relied upon to backward induct with mindful rationally, does not mean that their socially This interpretation is consistent with trust game data reported by Rigdon, et al (2007) in which subjects are allocated randomly between two repeat play treatments: in the control each trial rematches subjects in pairs at random; in the research treatment subjects are rank ordered on each trial by frequency of historical cooperation over the previous five decision trials, and then matched according to these "trust" and "trustworthy" scores.…”
Section: Money (It Is Not the Standard Interactive Game In Which Paysupporting
confidence: 78%
“…We address this in footnote 22 and repeat it here: Following Gunnthorsdottir, Houser, and McCabe (2007) and Rigdon, McCabe, and Smith (2007), we do not reveal to our subjects how their group is formed because our hypothesis is not about the rules of capture that people develop when they know they are combined with two other pairs who have the fewest or highest total number of strikes on attached whales in the previous six periods. Rather, the question is what rules, if any, spontaneous emerge amongst six similarly disposed people who happen to find themselves suddenly interacting with four other like-minded people.…”
Section: Appendix B Content Analysis Procedures and Results (Not Formentioning
confidence: 99%
“…Now Smith indeed also defends his thesis by such work, viz., an experiment conducted by Mary Rigdon, Kevin McCabe, and himself [17]. This experiment showed that people in an anonymous repeated PD play substantially more cooperatively when the experimenters secretly cluster the cooperators as the experiment proceeds.…”
Section: The One-shot Game Designmentioning
confidence: 99%
“…Then one individual sends a reliable signal about one's commitment to cooperate, for example, through facial expressions that are 16 For a brief historical account of the development of the Harambee, see Waithima [48], the introduction. 17 I borrow this wording from Francesco Guala who wrote: "More effort should be made in investigating how non-costly sanctions, backed up by adequate institutional scaffoldings, may be used to sustain positive reciprocity in a variety of real world settings" [6] p. 15). 18 But doesn't this Harambee history then function much like a script (Section 3)?…”
Section: The Loop In Real Lifementioning
confidence: 99%